2022
DOI: 10.1101/2022.05.24.493094
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human skeletal muscle ageing atlas

Abstract: Skeletal muscle ageing increases the incidence of age-associated frailty and sarcopenia in the elderly worldwide, leading to increased morbidity and mortality. However, our understanding of the cellular and molecular mechanisms of muscle ageing is still far from complete. Here, we generate a single-cell and single-nucleus transcriptomic atlas of skeletal muscle ageing from 15 donors across the adult human lifespan, accompanied by myofiber typing using imaging. Our atlas reveals ageing mechanisms acting across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…Another study focused on senescent cells in old mouse muscle, identified a population of p21-expressing myonuclei exhibiting senescent phenotypes, consistent with our results [ 53 ]. Lastly, a study probing intercostal muscle from young and old humans, using single cell and single nuclei RNA-seq, found inflammation, fiber typing changes and microenvironment alterations, to be distinct mechanisms driving muscle aging [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study focused on senescent cells in old mouse muscle, identified a population of p21-expressing myonuclei exhibiting senescent phenotypes, consistent with our results [ 53 ]. Lastly, a study probing intercostal muscle from young and old humans, using single cell and single nuclei RNA-seq, found inflammation, fiber typing changes and microenvironment alterations, to be distinct mechanisms driving muscle aging [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past ten years, the advanced single-cell transcriptomics analyses have enabled systemically dissecting and monitoring all cell type heterogeneity and their aging dynamics both in human (Barruet et al, 2020;De Micheli et al, 2020;Perez et al, 2022;Rubenstein et al, 2020) and model organisms (Dos Santos et al, 2020;Jing et al, 2022;Kim et al, 2020b;Petrany et al, 2020;Zhang et al, 2022d). With mammalian aging, skeletal muscle exhibits decrease in MuSCs, Schwann cells, and vascular cells but infiltration of various immune cells and fibroblasts (Kedlian et al, 2022), in parallel with physiological dysfunction and chronic inflammation. In addition, together with spatial transcriptomics (Wang et al, 2022f), new hallmarks of muscle aging driven by pro-inflammatory cytokines such as CCL2 (Kedlian et al, 2022;Moiseeva et al, 2023) may be defined.…”
Section: Cellular Alterationsmentioning
confidence: 99%
“…With mammalian aging, skeletal muscle exhibits decrease in MuSCs, Schwann cells, and vascular cells but infiltration of various immune cells and fibroblasts (Kedlian et al, 2022), in parallel with physiological dysfunction and chronic inflammation. In addition, together with spatial transcriptomics (Wang et al, 2022f), new hallmarks of muscle aging driven by pro-inflammatory cytokines such as CCL2 (Kedlian et al, 2022;Moiseeva et al, 2023) may be defined.…”
Section: Cellular Alterationsmentioning
confidence: 99%
“…While arterial and capillary ECs were shown to be strongly depleted in aged individuals, a drastic increase in veins expressing the proinflammatory cytokine CCL2 was observed in aged muscle. In line with this, CCL2 + veins and several other microenvironmental subpopulations of cells enriched for CCL2 (e.g., fibroblasts, smooth muscle cells, pericytes) were predicted to recruit different types of immune cells to muscle tissue in aged mice via its receptors (CCR2, CCR10) [ 55 ], again suggesting an overall increased pro-inflammatory environment in the aging muscular vasculature. Lastly, besides an upregulation of several immunoregulatory transcription factor (TF) activities (e.g., Rfx5, Nfat5 ), aging muscle ECs in the mouse were intriguingly shown to exhibit decreased activity of Arntl and Clock TFs [ 56 ], which are involved in regulating the circadian clock.…”
Section: Introductionmentioning
confidence: 89%